A spectrum of (Dis)Belief: Coronavirus frames in a rural midwestern town in the United States. (March 2021) - Koon, Adam D.; Mendenhall, Emily; Eich, Lori; Adams, Abby; Borus, Zach A.
Abstract: Community responses to the SARS-CoV-2, or "coronavirus" outbreaks of 2020 reveal a great deal about society. In the absence of government mandates, debates over issues such as mask mandates and social distancing activated conflicting moral beliefs, dividing communities. Policy scholars argue that such controversies represent fundamental frame conflicts, which arise from incommensurable worldviews, such as contested notions of "liberty" versus "equity". This article investigates frames people constructed to make sense of coronavirus and how this affected social behavior in 2020. We conducted an interpretive framing analysis using ethnographic data from a predominately white, conservative, and rural midwestern tourist town in the United States from June to August 2020. We collected semi-structured interviews with 87 community members, observed meetings, events, and daily life. We identified four frames that individuals constructed to make sense of coronavirus: Concern, Crisis, Constraint, and Conspiracy. Concern frames illustrated how some individuals are uniquely affected and thus protect themselves. Crisis frames recognized coronavirus as a pervasive and profound threat requiring unprecedented action. Constraint frames emphasized the coronavirus response as a threat to financial stability and personal growth that should be resisted. Conspiracy frames denied its biological basis and did not compel action. These four conflicting frames demonstrate how social fragmentation, based on conflicting values, led to an incomplete pandemic response in the absence of government mandates at the national, state, and local levels in rural America. These findings provide a social rationale for public health mandates, such as masking, school/business closures, and social distancing, when contested beliefs impede collective action. Highlights: The American coronavirus public health response revealed division and divergence. Without government COVID-19 mandates, conflicting moral beliefs divided American communities. Four frames emerged in the American Midwest: Concern, Crisis, Constraint, and Conspiracy. Social fragmentation, based on conflicting values, opened the floodgates to coronavirus.